2017
DOI: 10.1080/13811118.2017.1340856
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Religion, and Suicidality Among Veterans: A Qualitative Study

Abstract: This qualitative study explores the relationship between veterans' spirituality/religion and suicide ideation and attempts. Qualitative semi-structured interviews were conducted with 30 veterans who either endorsed chronic suicidal ideation or had made suicide attempt(s). Interviews explored the bi-directional relationship between spirituality/religion (e.g., beliefs, practices, and experiences), and suicide ideation and behaviors. Interviews were analyzed using thematic analysis. Veterans' responses indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We firmly believe that discussing religiosity with MDD subjects may offer insights into why some people are more likely to consider or not suicide, which may have implications for both patient care and the institution of effective suicide prevention strategies [24,87]. In several cases, the collaboration with spiritual care providers, such as priests and ecclesiastics, may enhance suicide prevention efforts [45,49].…”
Section: Discussionmentioning
confidence: 99%
“…We firmly believe that discussing religiosity with MDD subjects may offer insights into why some people are more likely to consider or not suicide, which may have implications for both patient care and the institution of effective suicide prevention strategies [24,87]. In several cases, the collaboration with spiritual care providers, such as priests and ecclesiastics, may enhance suicide prevention efforts [45,49].…”
Section: Discussionmentioning
confidence: 99%
“…27 The results of this study showed that the soldiers' SWB was high. Numerous studies in the USA, 28,29 (, Australia, 30 and Iran 1,31 revealed high levels of SWB in participants. One of the reasons for high SWB score of the Iranian military soldiers can be the cultural and social characteristics ruling this society; in Iran, spirituality is intertwined with the social, cultural, and family dimensions of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, spirituality, as a coping strategy, can play an important role in solving everyday problems and stressful issues in different situations. 32 In this respect, Lusk et al 28 showed that American people with deep spiritual beliefs had better mental health. They did not run away from work and responsibility and were steadfast in the field of organizational missions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Because of the uniqueness and subtlety of Wonogiri, it is necessary to use a qualitative approach to explore the characteristics, causality, and suicidal behavior in Wonogiri. A study by Lusk et al 12 indicates a complex relationship between spirituality/religion and suicidality. Therefore, suicidal behavior needs to be identified based on the experience of family members who had suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Based on this phenomenon, this study explores the characteristics, causality, and suicidal behavior among family members with suicide history, so that the incidence of suicidal behavior can be controlled and the number of suicides decreased. 12…”
Section: Introductionmentioning
confidence: 99%